Effect of Oil Cakes and Bio-agents Each Alone and in Combination for Management of Root Knot Nematode (Meloidogyne incognita) in Green Gram - Jena, Poornata; Sahoo, N. K.; Mahalik, J. K. (International Journal of Bio-resource and Stress Management, 2021)
A pot experiment was carried out in the net house of Department of Nematology, OUAT, Bhubaneswar, Odisha, India during June to August, 2017 on the application of oilcakes (mustard cake and neem cake) and bio-agents (Trichoderma viride, Glomus fasciculatum, Rhizobium leguminosarum) each alone and in combination for the management of root knot nematode (Meloidogyne incognita) in green gram. Result of the experiment indicated that soil application of mustard or neem cake @ 50 g m-2 with AM fungus (Glomus fasciculatum) @ 5 g m-² and seed treatment of Rhizobium @ 25 g kg-1 of green gram seed declined the root knot nematode population, number of galls plant-1, number of eggmass plant-1and root knot index with corresponding increase of plant growth parameters and chlorophyll content in green gram plant as compared to other treatments and untreated check. But integration of mustard cake @ 50 g m-2 at 2 weeks prior to sowing with AM fungus @ 5 g m-2 at 10 days before sowing and seed treatment of Rhizobium @ 25 g kg-1 green gram seed exhibited the lowest M. incognita population 200 cc soil-1 (153.33 J2), number of galls plant-1 (7.0), number of eggmass plant-1 (2.0) and root knot index (2.0) reflecting enhancement of plant growth parameters, number of pods (206.67%), number of nodules (691.17%) over untreated check. This integrated management module also recorded maximum increase in the availability of NPK content in soil and chlorophyll content as compared to other treatments.